Rising Wage Inequality, Rate of Return on Investment in Education and Cost of Education - Milenko Popović (Montenegrin Journal of Economics, 2007)
One of the most interesting facts about the growth of developed nations, especially of the US growth, in the last three decades is significant growth of the ratio of the wage of skilled labor to that of unskilled labor. At the same time, existing evidence seems to suggest that the ratio of the rate of return on investment in skilled labor to that of unskilled labor has stayed pretty stable. This contradicting trend in movement of two ratios is formally easy to explain. Being aware of the fact that all possible measures of the rate of return in education confront, in one way or another, differences in wages of different educational levels with the cost of reaching the concerned level of education, we can with certainty conclude that, in order to keep the rate of return ratio unchanged, the increase of wage ratio should be accompanied with adequate increase in the ratio of the cost of reaching a skilled level of education to the cost of reaching an unskilled level. This is something that follows from identity and as such cannot be questioned. The real question here refers to a possible source of relative increase in the cost of reaching skilled level of education. Possibilities are here enormous and every developed country presents a different story. The purpose of this article is to shed a light on one of the sources of education cost growth which is common to all developed countries and which can explain the greatest part of education cost ratio increase in all developed countries. In what follows we will show that the increase in the cost of education ratio is mostly due, first, to the fact that technological progress in industry of education is negligible, second, to the fact that “products” of industry of education are nontradeables, and third, to the increase of wage ratio itself.
Keywords: O11; O40; D31; J31; 330; inequality; growth; capital of education; costs of education; Income distribution; growth; Human capital; Education finance